Integrated analysis of ATAC-seq and RNA-seq reveals the chromatin accessibility and transcriptional landscape of immunoglobulin a nephropathy - Gao, Zhao-Xing (Clinical immunology (Orlando, Fla.), 2025)
Copyright © 2025 Elsevier Inc. All rights reserved.